KEBIJAKAN CUKAI KANTONG PLASTIK SEBAGAI DAMPAK EKSTERNALITAS LINGKUNGAN - Irmayani Irmayani; Syahril Syahril (JURNAL EKOMBIS, 2020)
Demand of plastic in Indonesia is increased from year to year even though plastic is the biggest waste that causes environmental damage. This study aims to find a solution so that plastic waste does not continue increasing by including external costs into production costs. External costs are cost of damage as a consequence of pollution. This result of this article is expected to be an evaluation in an effort to overcome people's dependence on plastic bags. In addition, it is considered as an alternative policy to regulate plastic usage. Recently plastic waste has become national and international issue. Therefore government intervention is required, for example, the prohibition of using plastic bags with certain contents or policy of tax for certain plastic products.Keywords : Plastic, , external costs, Tax